Zirconium amorphous material for sealing layer at bottom of glass melting furnace and preparation method of zirconium amorphous material
By using high-purity electromelting white corundum particles and zirconium ambiguous materials with specific alumina and zirconium powder, the existing glass melting kiln pool bottom sealing materials have been solved, and the volume stability and efficient sealing effect of the sealing layer are achieved.
Patent Information
- Application Number
- CN202510336106.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing glass melting kiln bottom sealing materials have problems such as scaling shrinkage, cracking, and poor anti-glass liquid corrosion performance at high temperatures, resulting in poor sealing effect and may cause kiln safety accidents.
Zirconium amorphous materials composed of high-purity electromelted white corundum particles, specific proportions of aluminum oxide, zircon powder and zircon sand are used to form phases such as mullite through specific ratios and preparation methods to ensure that the material is in a zero-expanded or slightly expanded state during the sintering process, and enhance the resistance to glass liquid corrosion.
The volume stability of the sealing layer is achieved, cracks and delamination are avoided, the sealing effect and anti-glass liquid corrosion performance are improved, and it can withstand high temperatures above 1400°C for a long time.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of melting furnace pool bottom sealing materials, and in particular to a zirconium amorphous material for a glass melting furnace pool bottom sealing layer and a preparation method thereof. Background Art
[0002] The sealing layer of the bottom of the glass melting furnace is a vital part of the glass melting furnace. Its main functions are to prevent glass liquid leakage, reduce heat loss, protect the kiln structure and extend the service life of the melting furnace. With the continuous development of glass manufacturing technology, the performance requirements for the bottom sealing layer of the tank are getting higher and higher. It is required that it can be stable in volume, not expand, shrink or crack during the heating process and under long-term high temperature, and can resist the erosion of high-temperature glass liquid and metal; and can withstand high temperatures above 1400℃ for a long time, have sufficient compressive strength and flexural strength to withstand the pressure of glass liquid; at the same time, the material must have good plasticity and adhesion to facilitate ramming construction.
[0003] Fused zirconium corundum brick is one of the important refractory raw materials containing zirconium oxide. It is made by adding zircon sand, zirconium oxide or desiliconized zirconium and alkali powder to alumina and melting in an electric arc furnace. The main crystal phase of fused zirconium corundum is α-Al2O3, the secondary crystal phase is baddeleyite, and there is a small amount of glass phase. The appearance is generally yellow-brown and very dense. According to the different ZrO2 content, fused zirconium corundum can be divided into low fused zirconium corundum (ZrO2 content is about 10-15wt.%), medium fused zirconium corundum (ZrO2 content is about 25wt.%) and high fused zirconium corundum (ZrO2 content is about 40wt.%). Fused zirconium corundum bricks are widely used in the bottom and wall of glass kiln pools due to their excellent resistance to glass erosion. The amorphous zirconium sealing layer material used in conjunction with the fused zirconium corundum pool bottom paving tiles also plays a vital role in the safety of the kiln structure. Only when the fused zirconium corundum pool bottom paving tiles, joints and sealing layer are combined into a closed and inseparable whole can the melting furnace be effectively prevented from leaking and the life of the melting furnace be extended.
[0004] Chinese invention patent CN106810282A discloses a method for producing ramming materials using fused zirconium corundum waste bricks, which uses fused zirconium corundum waste bricks recovered from glass kilns, and obtains fused zirconium corundum aggregates after sorting, quenching, crushing, and screening, and then evenly mixes the fused zirconium corundum aggregates with zircon powder, binders, and additives to obtain ramming materials. Although this method realizes the recycling of fused zirconium corundum waste bricks from glass kilns, in order to eliminate the glass and alkaline substances attached to the recycled fused zirconium corundum waste bricks, a large amount of carboxylic acid or organic acid needs to be introduced into the powder, and a large amount of additives is used; during construction, the alkaline substances attached to the recycled materials will produce a neutralization reaction with the used binder phosphate to release heat, causing construction abnormalities; in addition, due to the excessively high impurity content of the recycled materials, the high-temperature performance of the final product is poor and will cause pollution to the glass.
[0005] Chinese invention patent CN119390446A discloses a method for preparing zircon ramming material for glass kiln, which uses zircon as refractory aggregate, fused zircon corundum powder as refractory powder, alumina as additive, and silica sol-alumina composite binder instead of traditional silicate as binder, and prepares the ramming material for glass kiln through batching, mixing, molding, drying and sintering. In this patent, zircon aggregate needs to be artificially secondary molded, sintered and crushed into required particles, and fused zircon corundum powder needs to be electro-melted, crushed and ground, and the preparation process is complicated and easy to introduce impurities. In addition, this patent uses a ramming material with different crystal phase from paving bricks and high impurity content such as Fe2O3. Since it cannot be sintered with paving bricks to form a composite layer as a whole and has a high foaming rate at high temperature, its resistance to upward drilling erosion by glass liquid is poor.
[0006] In summary, the commonly used zirconium bottom sealing materials have the following problems: the bottom sealing materials are generally prepared with fused zirconium corundum materials, recycled fused zirconium corundum brick crushed materials, zircon brick crushed materials, etc. as the main raw materials. Due to the high content of R2O, Fe2O3 and other impurities in the products, the crystal phase is inconsistent with the paving bricks, and they cannot be sintered with the paving bricks at high temperatures to form a composite layer with a high overall and high foaming rate, and their resistance to upward drilling erosion by glass liquid is poor; in the kiln baking stage, the ramming material sealing layer shrinks greatly after being heated, and the sealing layer is subjected to the compressive stress of the upper paving bricks and the shrinkage stress of the ramming material during firing, and the sealing layer cracks, causing the bottom sealing material to lose its sealing effect; in the kiln operation stage, after the high-temperature glass liquid invades the sealing layer from the gap of the paving bricks, the sealing layer reacts with the glass liquid, and bubbles are easily generated, resulting in bubble defects in the glass products, and even the glass liquid reacts violently with the sealing layer, causing the upper fused zirconium corundum pool bottom paving bricks to arch upward, causing kiln safety accidents.
[0007] Therefore, it is necessary to develop new zirconium amorphous materials for the glass melting furnace bottom sealing layer to solve the above problems. Summary of the invention
[0008] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a zirconium amorphous material for a glass melting furnace pool bottom sealing layer and a preparation method thereof, wherein the zirconium amorphous material is in a zero expansion or micro-expansion state during the drying and sintering process, the sealing layer itself will not crack and will not be delaminated with the paving tiles, and the sealing effect is better; and after sintering, the volume density is high, and the material has high resistance to glass liquid erosion and glass liquid permeability.
[0009] The technical solution of the present invention is: On the one hand, the present invention provides a zirconium amorphous material for a glass melting furnace bottom sealing layer, comprising the following components in parts by weight: 18-52 parts of fused white corundum particles, 3-15 parts of aluminum oxide, 8-35 parts of zircon sand, 22-47 parts of zircon powder, 3-10 parts of clay fine powder, and 4-8 parts of a binder; wherein the aluminum oxide crystal form is α-Al2O3, including aluminum oxide I and aluminum oxide II, 2000 mesh < aluminum oxide I particle size ≤ 325 mesh, aluminum oxide II particle size ≤ 2000 mesh, and the mass ratio of aluminum oxide I to aluminum oxide II is (2-5):1.
[0010] Preferably, in the fused white corundum particles, Al2O3>99wt.%, Fe2O3<0.1wt.%, and particle size 1mm≤≤5mm.
[0011] Preferably, in the alumina, Al2O3>99wt.%, Fe2O3<0.05wt.%.
[0012] Preferably, in the zircon sand, ZrO2>63wt.%, Fe2O3<1wt.%, TiO2<1.5wt.%, and particle size of 120 mesh≤≤80 mesh.
[0013] Preferably, in the zircon powder, ZrO2>63wt.%, Fe2O3<1wt.%, TiO2<1.5wt.%, and particle size ≤325 mesh.
[0014] Preferably, the clay fine powder is Suzhou clay, with Al2O3>36wt.%, Fe2O3<1.2wt.%, and particle size ≤325 mesh.
[0015] Preferably, the binder is aluminum dihydrogen phosphate powder with a particle size of ≤0.1 mm.
[0016] On the other hand, the present invention provides a method for preparing the above-mentioned zirconium amorphous material for the bottom sealing layer of a glass melting furnace, comprising the following steps: S1 Raw material mixing: put all components into a mixer and dry mix them, then add 3-5wt.% water and mix them; S2 Ramming construction: Pour the mixed mud into the mold and ram it until the surface is smooth; S3 curing and hardening: After the construction is completed, it is naturally cured for 24-48 hours to harden, and the sample body is obtained after demoulding; S4 drying and sintering: drying the sample body and then sintering it to obtain the zirconium amorphous material for the bottom sealing layer of the glass melting furnace.
[0017] Preferably, in step S4, the drying temperature is 100-120°C, and the drying time is more than 12 hours; the sintering temperature is 1200-1400°C, and the insulation time is more than 3 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The glass melting furnace bottom sealing layer of the present invention uses zirconium amorphous material, adopts high-purity raw material fused white corundum particles as aggregate, and specific proportions of aluminum oxide I, aluminum oxide II, zircon powder and zircon sand as matrix. During long-term use, the zircon sand and zircon powder in the matrix gradually react with specific proportions of aluminum oxide I and aluminum oxide II to form mullite, etc. The resulting volume expansion just offsets the firing shrinkage of the sealing layer, so that the overall volume of the material is always in a zero expansion or micro-expansion state. The sealing layer itself will not crack and will not be delaminated with the paving bricks. It can be sintered with the paving bricks to form an integral composite layer, and the sealing effect is good.
[0019] 2. The raw materials and their proportions used in the present invention make the main crystal phase of the particles after sintering basically consistent with the fused zirconium corundum paving bricks, and the main crystal phase of the matrix part is also consistent with the fused zirconium corundum paving bricks. The matrix part is corundum, zirconium oxide, and mullite phases, with almost no glass phase, and low impurity content, with the advantages of good resistance to glass liquid erosion, low foaming and low permeability. At the same time, after sintering, the volume density is high, the strength is high, the permanent line change is small, the volume stability is good at high temperature, and it can withstand high temperatures above 1400°C for a long time.
[0020] 3. The glass melting furnace bottom sealing layer of the present invention uses a zirconium amorphous material, which has good plasticity and adhesion and is easy to ram and construct. DETAILED DESCRIPTION
[0021] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0022] The raw materials in the following examples and comparative examples are all commercially available raw materials. The chemical composition test results and particle size of each raw material are shown in Table 1-2: Table 1 Chemical composition test results of each raw material
[0023] Table 2 Particle size of each raw material
[0024] Example 1 The zirconium amorphous material for the glass melting furnace bottom sealing layer of this embodiment includes the following components in parts by weight: 42 parts of fused white corundum particles, 8 parts of aluminum oxide, 20 parts of zircon sand, 25 parts of zircon powder, 5 parts of Suzhou soil, and 6 parts of aluminum dihydrogen phosphate powder; wherein the aluminum oxide crystal form is α-Al2O3, and the mass ratio of aluminum oxide I to aluminum oxide II is 3:1; the particle size of the aluminum dihydrogen phosphate powder is ≤0.1mm.
[0025] The method for preparing the amorphous zirconium material for the glass melting furnace bottom sealing layer of the present embodiment comprises the following steps: S1 Raw material mixing: Put all components into a mixer and dry mix for 3 minutes, then add 3.5wt.% water and mix for 10 minutes; S2 Ramming construction: Pour the mixed mud into a 230mm×65mm×65mm mold and use a vibrator to ram until the surface is smooth; S3 curing and hardening: After the construction is completed, it is naturally cured for 24 hours to harden, and the sample body is obtained after demoulding; S4 drying and sintering: Place the sample body in a drying oven and dry it at 100°C for 48 hours. Place the dried body in a kiln and sinter it at a sintering temperature of 1400°C for 3 hours.
[0026] Example 2 The zirconium amorphous material for the glass melting furnace bottom sealing layer of this embodiment includes the following components in parts by weight: 30 parts of fused white corundum particles, 10 parts of aluminum oxide, 10 parts of zircon sand, 47 parts of zircon powder, 3 parts of Suzhou soil, and 7 parts of aluminum dihydrogen phosphate powder; wherein the aluminum oxide crystal form is α-Al2O3, and the mass ratio of aluminum oxide I to aluminum oxide II is 7:3; the particle size of the aluminum dihydrogen phosphate powder is ≤0.1 mm.
[0027] The method for preparing the amorphous zirconium material for the glass melting furnace bottom sealing layer of the present embodiment comprises the following steps: S1 Raw material mixing: Put all components into a mixer and dry mix for 3 minutes, then add 3wt.% water and mix for 10 minutes; S2 Ramming construction: Pour the mixed mud into a 230mm×65mm×65mm mold and use a vibrator to ram until the surface is smooth; S3 curing and hardening: After the construction is completed, it is naturally cured for 30 hours to harden, and the sample body is obtained after demoulding; S4 drying and sintering: Place the sample body in a drying oven and dry it at 120°C for 12 hours. Place the dried body in a kiln and sinter it at a sintering temperature of 1350°C for 5 hours.
[0028] Example 3 The zirconium amorphous material for the glass melting furnace bottom sealing layer of this embodiment includes the following components in parts by weight: 37 parts of fused white corundum particles, 8 parts of aluminum oxide, 25 parts of zircon sand, 27 parts of zircon powder, 3 parts of Suzhou soil, and 6 parts of aluminum dihydrogen phosphate powder; wherein the aluminum oxide crystal form is α-Al2O3, and the mass ratio of aluminum oxide I to aluminum oxide II is 3:1; the particle size of the aluminum dihydrogen phosphate powder is ≤0.1mm.
[0029] The method for preparing the amorphous zirconium material for the glass melting furnace bottom sealing layer of the present embodiment comprises the following steps: S1 Raw material mixing: Put all components into a mixer and dry mix for 3 minutes, then add 5wt.% water and mix for 10 minutes; S2 Ramming construction: Pour the mixed mud into a 230mm×65mm×65mm mold and use a vibrator to ram until the surface is smooth; S3 curing and hardening: After the construction is completed, it is naturally cured for 48 hours to harden, and the sample body is obtained after demoulding; S4 drying and sintering: Place the sample body in a drying oven and dry it at 110°C for 18 hours. Place the dried body in a kiln and sinter it at a sintering temperature of 1200°C for 12 hours.
[0030] Example 4 The zirconium amorphous material for the glass melting furnace bottom sealing layer of this embodiment includes the following components in parts by weight: 18 parts of fused white corundum particles, 15 parts of aluminum oxide, 35 parts of zircon sand, 27 parts of zircon powder, 5 parts of Suzhou soil, and 8 parts of aluminum dihydrogen phosphate powder; wherein the aluminum oxide crystal form is α-Al2O3, and the mass ratio of aluminum oxide I to aluminum oxide II is 5:1; the particle size of the aluminum dihydrogen phosphate powder is ≤0.1mm.
[0031] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in this embodiment is the same as that in Example 1.
[0032] Example 5 The zirconium amorphous material for the glass melting furnace bottom sealing layer of this embodiment includes the following components in parts by weight: 45 parts of fused white corundum particles, 5 parts of aluminum oxide, 20 parts of zircon sand, 22 parts of zircon powder, 8 parts of Suzhou soil, and 5 parts of aluminum dihydrogen phosphate powder; wherein the aluminum oxide crystal form is α-Al2O3, and the mass ratio of aluminum oxide I to aluminum oxide II is 4:1; the particle size of the aluminum dihydrogen phosphate powder is ≤0.1mm.
[0033] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in this embodiment is the same as that in Example 1.
[0034] Example 6 The zirconium amorphous material for the glass melting furnace bottom sealing layer of this embodiment includes the following components in parts by weight: 52 parts of fused white corundum particles, 3 parts of aluminum oxide, 8 parts of zircon sand, 27 parts of zircon powder, 10 parts of Suzhou soil, and 4 parts of aluminum dihydrogen phosphate powder; wherein the aluminum oxide crystal form is α-Al2O3, and the mass ratio of aluminum oxide I to aluminum oxide II is 2:1; the particle size of the aluminum dihydrogen phosphate powder is ≤0.1 mm.
[0035] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in this embodiment is the same as that in Example 4.
[0036] Comparative Example 1 The zirconium amorphous material for the glass melting furnace bottom sealing layer of Comparative Example 1 includes the following components in parts by weight: 95 parts of fused zirconium corundum brick particles and fine powder, 5 parts of Suzhou soil, and 6 parts of dihydrogen aluminum phosphate powder, wherein the particle size of the dihydrogen aluminum phosphate powder is ≤0.1 mm.
[0037] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in Comparative Example 1 is the same as that in Example 1.
[0038] Comparative Example 2 The zirconium amorphous material for the glass melting furnace bottom sealing layer of Comparative Example 2 includes the following components in parts by weight: 95 parts of recycled fused zirconium corundum brick particles and fine powder, 5 parts of Suzhou soil, and 6 parts of dihydrogen aluminum phosphate powder, wherein the particle size of the dihydrogen aluminum phosphate powder is ≤0.1 mm.
[0039] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in Comparative Example 2 is the same as that in Example 1.
[0040] Comparative Example 3 The zirconium amorphous material for the glass melting furnace bottom sealing layer of Comparative Example 3 includes the following components in parts by weight: 95 parts of zircon brick particles and fine powder, 5 parts of Suzhou soil, and 6 parts of dihydrogen aluminum phosphate powder, wherein the particle size of the dihydrogen aluminum phosphate powder is ≤0.1 mm.
[0041] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in Comparative Example 3 is the same as that in Example 1.
[0042] Comparative Example 4 The difference from Example 1 is that fused zirconium corundum brick particles are used instead of the fused white corundum particles in Example 1.
[0043] Comparative Example 5 The difference from Example 1 is that zircon brick particles are used instead of the fused white corundum particles in Example 1.
[0044] Comparative Example 6 The difference from Example 1 is that the mass ratio of aluminum oxide I to aluminum oxide II is 7:1.
[0045] Comparative Example 7 The difference from Example 1 is that the mass ratio of aluminum oxide I to aluminum oxide II is 1:1.
[0046] Comparative Example 8 The difference from Example 1 is that aluminum oxide I is used instead of aluminum oxide II.
[0047] Comparative Example 9 The difference from Example 1 is that aluminum oxide II is used instead of aluminum oxide I.
[0048] Comparative Example 10 The difference from Example 1 is that activated alumina with a crystal form of γ-Al2O3 is used to replace the alumina with a crystal form of α-Al2O3 in Example 1.
[0049] Comparative Example 11 The zirconium amorphous material for the glass melting furnace bottom sealing layer of Comparative Example 11 includes the following components in parts by weight: 42 parts of fused white corundum particles, 20 parts of zircon sand, 33 parts of zircon powder, 5 parts of Suzhou soil, and 6 parts of dihydrogen aluminum phosphate powder, and the particle size of the dihydrogen aluminum phosphate powder is ≤0.1 mm.
[0050] The preparation method of the zirconium amorphous material for the glass melting furnace bottom sealing layer in Comparative Example 11 is the same as that in Example 1.
[0051] The performance tests were carried out on the zirconium amorphous material for the bottom sealing layer of the glass melting furnace prepared in Examples 1-6 and Comparative Examples 1-11. The apparent porosity and bulk density were tested in accordance with GB / T 2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products; the compressive strength was tested in accordance with GB / T 5072-2023 Test method for compressive strength of refractory materials at room temperature; the compressive creep rate was tested in accordance with GB / T 5073-2005 Test method for compressive creep of refractory materials; the erosion rate was tested in accordance with JC / T806-2017 Test method for static resistance to glass liquid erosion of refractory materials for glass melting furnaces; the thickness of the permeable layer was directly measured by the discoloration layer of the cut surface of the test strip after the erosion test; the foaming index was measured by 1200°C × 3h After sintering, cut out a 70mm×70mm×65mm test block, drill a hole with a diameter of 30mm and a depth of 30mm in the middle, put in glass and cover with a cover plate of the same material, heat up to the test temperature at a rate of 200℃ / h, keep warm for 12 hours, cool the sample to room temperature with the furnace, cut a 10mm thick slice from the middle of the crucible, and observe the number of bubbles in the glass under a microscope; the line change rate is tested in accordance with "YBT 5203-1993 Test Method for Line Change Rate of Dense Refractory Castables". The test results are shown in Table 3-4: Table 3 Performance test results of zirconium amorphous material for glass melting furnace bottom sealing layer of Examples 1-6
[0052] Table 4 Performance test results of zirconium amorphous materials for glass melting furnace bottom sealing layer of comparative examples 1-11
[0053] It can be seen from Table 3 that the zirconium amorphous material for the glass melting furnace bottom sealing layer obtained in Examples 1-6 has a positive linear change rate at 100°C×24h and 800°C×24h, that is, it is in a slightly expanded state during the drying stage. The linear change rate at 1200°C×3h is between 0.08% and 0.36%, and the volume expands slightly after sintering; the apparent porosity after sintering at 1200°C×3h is 14.3-15.1%, and the volume density is 3.01-3.05 g / cm 3 , compressive strength is 80-99MPa; 1300℃×0.2MPa compressive creep rate is 0.06-0.46%; 1350℃×48h erosion rate is 0.97-1.5mm / 24h; 1350℃×48h penetration layer thickness is 1.24-1.66mm; 1200℃×12h foaming index is 1-2. Comparing Example 1 with Examples 2-6 in Table 3, it can be seen that the performance difference of the prepared zirconium amorphous material is not much when the proportion of components such as fused white corundum particles is appropriately adjusted within the scope defined by the present invention.
[0054] By comparing Examples 1-6 and Comparative Examples 1-3 in Table 4, it can be seen that the zirconium amorphous material for the bottom sealing layer of the glass melting furnace prepared by using fused zirconium corundum bricks, recycled fused zirconium corundum bricks, and particles and fine powder obtained by crushing zircon bricks as aggregates and matrix has a positive or slightly contracted linear change rate at 100℃×24h, 800℃×24h, and 1200℃×3h, but the apparent porosity after sintering at 1200℃×3h is 20.5-24.2%, and the volume density is only 2.56-3.01g / cm 3 , the compressive strength is only 30-48MPa, and the creep rate at 1300℃×0.2MPa is negative, ranging from -1.48% to -1.24%; the erosion rate at 1350℃×48h is 2.18-3.1mm / 24h, the thickness of the permeable layer reaches 3.52-4.66mm, and the foaming index at 1200℃×12h is 3-5. Although the main crystal phases of Comparative Examples 1 and 2 before sintering are similar to those of fused zirconium corundum pool bottom paving bricks, the contents of R2O, Fe2O3 and other impurities are high, and the sintering activity is poor. After sintering, they show poor corrosion resistance, high foaming rate and poor stability at high temperature. The main crystal phase of Comparative Example 3 before sintering is quite different from that of fused zirconium corundum pool bottom paving bricks. The decomposition of zircon particles in alkaline components leads to poor overall corrosion resistance, poor stability at high temperature and high foaming rate. After sintering, it is difficult to sinter with paving bricks into a composite layer as a whole.
[0055] By comparing Example 1 with Comparative Examples 4-5, it can be seen that the zirconium amorphous material for the bottom sealing layer of the glass melting furnace pool made by using fused zirconium corundum brick particles and zircon brick particles instead of fused white corundum particles has a positive linear change rate at 100℃×24h, 800℃×24h, and 1200℃×3h, showing a slight expansion. After sintering at 1200℃×3h, the apparent porosity, volume density, and compressive strength are equivalent to those of Example 1, but the 1300℃×0.2MPa compressive creep rate is negative, indicating that its volume is unstable under high temperature and high pressure. Further comparing Example 1 with Comparative Examples 4-5, the 1350℃×48h erosion rate, permeation layer thickness, and foaming index of Comparative Examples 4-5 are significantly increased, indicating that the present invention uses fused white corundum particles matched with matrix fine powder, which has obvious advantages in volume stability and low foaming at high temperature.
[0056] By comparing Example 1 with Comparative Examples 6-9, it can be seen that when the ratio of aluminum oxide I to aluminum oxide II exceeds the specified range of the present invention, the mullite reaction is weakened, the phase change volume expansion is insufficient to offset the sintering shrinkage of the material, the volume shrinkage after sintering is large, and the 1300℃×0.2MPa compressive creep rate is negative. Although its apparent porosity, volume density, compressive strength, erosion resistance and foaming property after sintering at 1200℃×3h are comparable to those of Example 1, its high-temperature volume stability is poor, and it is difficult to form a stable composite layer with the fused zirconium corundum pool bottom paving bricks.
[0057] Comparative Example 10 is a zirconium amorphous material for the bottom sealing layer of a glass melting furnace made of activated alumina with γ-Al2O3 crystal form. It burst when dried to 652°C. The main reason is that the activated alumina absorbs moisture during the batching and construction process. During the drying and calcining process, the crystal form changes to α-Al2O3, and a large amount of bound water is discharged. The fast drying and heating speed leads to the failure to discharge the moisture in the brick in time, resulting in bursting.
[0058] By comparing Example 1 with Comparative Example 11, it can be seen that in Comparative Example 11, α-Al2O3 crystal alumina is not used as the matrix, and the matrix is entirely made of zircon powder and clay fine powder. The line change rates at 100°C×24h, 800°C×24h, and 1200°C×3h are all negative, and the volume shrinks during the firing process. The mullite reaction is weakened by the reaction of Al2O3 provided by the clay fine powder with zircon sand and zircon powder, and the phase change volume expansion is not enough to offset the firing shrinkage of the material. The volume shrinkage after sintering is large; and the erosion rate at 1350°C×48h, the thickness of the penetration layer, and the foaming index are significantly increased compared with those in Example 1.
Claims
1. Zirconium amorphous material for the bottom sealing layer of a glass melting furnace, characterized in that: The invention comprises the following components in parts by weight: 18-52 parts of fused white corundum particles, 3-15 parts of alumina, 8-35 parts of zircon sand, 22-47 parts of zircon powder, 3-10 parts of clay fine powder, and 4-8 parts of a binder; wherein the alumina crystal form is α-Al2O3, comprising alumina I and alumina II, 2000 mesh < alumina I particle size ≤ 325 mesh, alumina II particle size ≤ 2000 mesh, and the mass ratio of alumina I to alumina II is (2-5):
1.
2. The zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 1, characterized in that: In the fused white corundum particles, Al2O3>99wt.%, Fe2O3<0.1wt.%, and particle size 1mm≤≤5mm.
3. The zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 1, characterized in that: In the alumina, Al2O3>99wt.%, Fe2O3<0.05wt.%.
4. The zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 1, characterized in that: In the zircon sand, ZrO2>63wt.%, Fe2O3<1wt.%, TiO2<1.5wt.%, and particle size of 120 mesh≤≤80 mesh.
5. The zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 1, characterized in that: In the zircon powder, ZrO2>63wt.%, Fe2O3<1wt.%, TiO2<1.5wt.%, and particle size ≤325 mesh.
6. The zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 1, characterized in that: The clay fine powder is Suzhou clay, Al2O3>36wt.%, Fe2O3<1.2wt.%, and particle size ≤325 mesh.
7. The zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 1, characterized in that: The binder is aluminum dihydrogen phosphate powder with a particle size of ≤0.1 mm.
8. The method for preparing the zirconium amorphous material for the glass melting furnace bottom sealing layer according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1 Raw material mixing: put all components into a mixer and dry mix them, then add 3-5wt.% water and mix them; S2 Ramming construction: Pour the mixed mud into the mold and ram it until the surface is smooth; S3 curing and hardening: After the construction is completed, it is naturally cured for 24-48 hours to harden, and the sample body is obtained after demoulding; S4 drying and sintering: drying the sample body and then sintering it to obtain the zirconium amorphous material for the bottom sealing layer of the glass melting furnace.
9. The method for preparing the zirconium amorphous material for the glass melting furnace bottom sealing layer according to claim 8, characterized in that: In step S4, the drying temperature is 100-120°C, and the drying time is more than 12 hours; the sintering temperature is 1200-1400°C, and the heat preservation time is more than 3 hours.
Citation Information
Patent Citations
Preparation method of zirconite ramming material for glass kiln
CN119390446A
Magnesium-calcium-zirconium slag non-sticking spraying coating
CN101121831A
Method for producing ramming material by utilizing electrofused zirconium corundum waste brick
CN106810282A
Zirconium hot repair material capable of being stored for long time and preparation method thereof
CN115611618A
Rotary tube for forming medium borosilicate glass tube and preparation method of rotary tube
CN117142843A